Study of the relationship between psycho-emotional wellbeing and personal qualities in Ukrainian youth: Ways of overcoming - Ivanchenko, Andreyanna; Zaika, Evgenij; Timchenko, Olexander; Costa, Massimiliano; Perepeliuk, Tetiana; Mytnyk, Alexander (Psychology and Behavioral Science International Journal, 2023)
Objectives. There is enough information about personal state and characteristics of the students from different countries, but about Ukrainian Senior school pupils and university students is completely missing. For the first time, the issue of stressful psychosomatic consequences for Ukrainian youth health is raised in world research. Methods. To assess wellbeing, anxiety, value orientations and behavior types in 216 youth (school/university participants) four standardized Instruments were used. Additionally, with other young/adult participants (n = 307), the method of conversation was used in order to establish their reaction to the ongoing Russian military aggression in Ukraine, and to find out the ways for prevention-rehabilitation the psycho-emotional state of all participants. Results and Conclusion. The greater anxiety, the more often competitive behavior. Wellbeing is negatively associated with competition behavior; anxiety is positively linked with adaptation. The youngest participants showed the worst state of health, higher anxiety and cooperative behavior. During the war unleashed by Russia, Ukrainians, on the one hand, were strongly motivated, aimed at the speedy cessation of hostilities which strengthened, encouraged them psycho-emotionally, on the other hand, needed special psychological support and help. High value orientations are combined with high conflict resolution. Special preventive-recovery activities were carried out with different categories of the population: refugees, people left in the war zone and their families, militaries, rescuers, medical personnel. Limitations. Findings on the anxiety and wellbeing interconnected with value orientations require clarification. Correctional-rehabilitation work efficiency provided to the participants suffered because of the hostilities need experimental-statistical confirmation.
Keywords: wellbeing; anxiety and psychological overload; value orientations; behavior types in conflicts; additional coping means